The Exercise and Sports Science Australia position statement: Exercise medicine in cancer management - Hayes, Sandra C. (2023)
Since Exercise and Sports Science Australia (ESSA) ﬁrst published its position statement on exercise guidelines for people with cancer, there has been exponential growth in research evaluating the role of exercise pre-, during and post-cancer treatment. Design and Methods: The purpose of this report is to use the current scientiﬁc evidence, alongside clinical experience and exercise science principles to update ESSA’s position statement on cancer-speciﬁc exercise prescription. Results: Reported in this position statement is a summary of the beneﬁts accrued through exercise following a cancer diagnosis and the strengths and limitations of this evidence-base. An exercise prescription framework is then proposed to enable the application of cancer-speciﬁc considerations for individualisation, speciﬁcity, safety, feasibility and progression of exercise for all patients. Additional speciﬁc exercise prescription considerations are provided for the presence of haematological, musculoskeletal, systemic, cardiovascular, lymphatic, gastrointestinal, genitourinary and neurological disease- and treatment-related concerns, as well as presence of co-morbid chronic disease. Further, we also identify and discuss cancer-speciﬁc pragmatic issues and barriers requiring consideration for exercise prescription. Conclusions: While for the majority, multimodal, moderate to high intensity exercise will be appropriate, there is no set prescription and total weekly dosage that would be considered evidence-based for all cancer patients. Targeted exercise prescription, which includes the provision of behaviour change advice and support, is needed to ensure greatest beneﬁt (as deﬁned by the patient) in the short and longer term, with low risk of harm.